Financial sector-output dynamics in the euro area: Non-linearities reconsidered - Frauke Schleer; Willi Semmler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We analyze the feedback mechanisms between economic downturns and financial stress for euro area countries. Our study employs newly constructed financial condition indices that incorporate extensively banking variables. We apply a nonlinear Vector Smooth Transition Autoregressive (VSTAR) model for investigating instabilities in the financial sector-output linkages. The VSTAR model appears appropriate since it allows for smooth regime changes and asymmetric dynamics. We find that regime-switching takes place rather smoothly which dampens the negative output response after a shock in the financial sector in the selected euro area countries. Moreover, linearity cannot be rejected for all countries over some extensive time period questioning non-linearities in the financial sector-output nexus as unambiguous feature. In particular, we show that the negative effect of financial stress on output typically observed is not always present. This holds specifically for the time before the Lehman collapse, even if this is a model-defined high stress regime. After the collapse, we observe strong amplification mechanisms. This suggests that events leading to a strong economic breakdown are rare but large events and related to financial cycles which exhibit low frequency.
urn:nbn:de:bsz:180-madoc-347106
Keywords: E2; E44; G01; 330; Vector STAR; financial stress; financial cycle; real economy; regime-switching; euro area